Implementation Of Intercultural Learning In English Language Learning In SMAIT Asy-Syukriyyah Tangerang - Setyawan, Aris; Muin, Muhammad Tamsil (STAI Asy-Syukriyyah, 2023)
There is nothing wrong with using English as a knowledge-generating language alongside Indonesian. The most important part is that we as an Indonesian-speaking community must be able to choose and sort out the elements of English that we want to be included in Indonesian without forgetting our identity as Indonesians. Indonesian people as users of the Indonesian language, use Indonesian. Therefore, we need an innovation in foreign language learning (English) that prioritizes local cultural elements so that students only learn elements of the foreign language. However, the learning content still includes elements of local Indonesian culture. Two things can be done as a form of innovation in learning English that can maintain noble Indonesian values, namely by learning with an intercultural perspective. With this model, students who study a foreign language will not necessarily take on the cultural values of native speakers. Still, rather they will have a comparison of values with the students' local culture and students will be able to take the best attitude from the foreign language learning process.